2007
DOI: 10.1096/fj.07-8628com
|View full text |Cite
|
Sign up to set email alerts
|

Human hair follicles are an extrarenal source and a nonhematopoietic target of erythropoietin

Abstract: Erythropoietin primarily serves as an essential growth factor for erythrocyte precursor cells. However, there is increasing evidence that erythropoietin (EPO)/EPO receptor (EPO-R) signaling operates as a potential tissue-protective system outside the bone marrow. Arguing that growing hair follicles (HF) are among the most rapidly proliferating tissues, we have here explored whether human HFs are sources of EPO and targets of EPO-R-mediated signaling. Human scalp skin and microdissected HFs were assessed for EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 56 publications
4
77
1
1
Order By: Relevance
“…Both EPO and EPOR transcripts were detected in hair bulbs of hair follicles. 19 In addition, EPO-like immunoreactivity was observed in hair follicle epithelium and in large blood vessels of human scalp. 19 Moreover, in vitro studies demonstrated the expression of EPOR by melanocytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both EPO and EPOR transcripts were detected in hair bulbs of hair follicles. 19 In addition, EPO-like immunoreactivity was observed in hair follicle epithelium and in large blood vessels of human scalp. 19 Moreover, in vitro studies demonstrated the expression of EPOR by melanocytes.…”
Section: Discussionmentioning
confidence: 96%
“…19 In addition, EPO-like immunoreactivity was observed in hair follicle epithelium and in large blood vessels of human scalp. 19 Moreover, in vitro studies demonstrated the expression of EPOR by melanocytes. 20 In this study, we demonstrate that non-wounded and wounded skin of the mouse as well as murine primary fibroblasts and keratinocytes express EPOR.…”
Section: Discussionmentioning
confidence: 96%
“…6 Moreover, a number of studies have reported that rhEPO affects the proliferation and differentiation of erythroid progenitor cells in hematopoietic organs, as well as nonhematopoietic cell types and organs, and plays a central role in tissue protection. [7][8][9][10][11] Although these reports have had encouraging outcomes, the lack of proof of common β subunit receptor (βCR) expression as the relevant tissue-based target for rhEPO in wound repair has been an important but missing link to explain the success of rhEPO in skin wound regeneration. In contrast with the homodimer hematopoietic EPO receptor (EPOR), 12 the tissue protective receptor is postulated to be a heterodimer formed by the EPO receptor in assembly with the βCR subunit, otherwise known as CD131, which is also used by other type I cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…13 NO is an enzymatic product from L-arginine that mediates numerous biological actions through the activation of cyclic guanosine monophosphate, which inhibits intracellular calcium release and induces smooth muscle relaxation. 14 As EPO and its receptor are also present in human skin, 15 ischemic wound complications and tissue necrosis might be prevented by administration of EPO. Despite advances in surgical techniques, patients may still suffer from wound breakdown and ischemic necrosis.…”
mentioning
confidence: 99%